2006
DOI: 10.1007/s00330-006-0250-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, extension and characteristics of fluid-fluid levels in bone and soft tissue tumors

Abstract: The purpose of this study was to determine the prevalence, extension and signal characteristics of fluid-fluid levels in a large series of 700 bone and 700 soft tissue tumors. Out of a multi-institutional database, MRI of 700 consecutive patients with a bone tumor and MRI of 700 consecutive patients with a soft tissue neoplasm were retrospectively reviewed for the presence of fluid-fluid levels. Extension (single, multiple and proportion of the lesion occupied by fluid-fluid levels) and signal characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 18 publications
3
65
1
1
Order By: Relevance
“…Fluid-fluid levels have been observed in various benign or malignant tumors, such as bone and soft tissue tumors, schwannomas, and sarcomas (4,5). Nevertheless, few articles have reported fluid-fluid levels in sellar pathologic masses, and the value of fluid-fluid levels in the differential diagnosis of sellar lesions is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Fluid-fluid levels have been observed in various benign or malignant tumors, such as bone and soft tissue tumors, schwannomas, and sarcomas (4,5). Nevertheless, few articles have reported fluid-fluid levels in sellar pathologic masses, and the value of fluid-fluid levels in the differential diagnosis of sellar lesions is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…There is no dedicated study on the most common etiology of osseous lesions with FFLs in pediatric patients, to our knowledge. In addition, large studies that may have included some pediatric patients had not published their detailed results based on age groups, [5][6][7] and the current literature is mainly limited to published case reports. [9][10][11][12][13][14] There are only 2 case reports describing the presence of fluid-fluid level in LCH.…”
Section: Discussionmentioning
confidence: 99%
“…However, 2 large studies primarily in adult patients have demonstrated that ABCs are the most common etiology of osseous lesions with FFLs throughout the body. 5,6 Despite these data, the presence of FFLs remains a nonspecific finding and can be seen in a wide range of benign and malignant bone lesions, including fibrous dysplasia, telangiectatic osteosarcoma, osteoblastoma, simple bone cyst, lymphatic malformations, Ewing sarcoma, brown tumor, giant cell tumor, and chondroblastoma. [5][6][7][8][9] In this study, head CT and MR imaging of pediatric patients having skull lesions with FFLs were retrospectively reviewed with the aim of characterizing these lesions.…”
mentioning
confidence: 99%
“…Neoplastic fluid-fluid levels are observed in 2.7% of bone tumors and in 2.9% of soft tissue tumors. 5 However, fluid-fluid levels have been reported in various tumors, regardless of benignity or malignancy. 6 In soft tissue tumors, fluid-fluid levels have been reported in schwannomas, cavernous hemangiomas, and sarcomas (eg, in synovial sarcoma and angiosarcoma, and in malignant fibrous histiocytosis).…”
Section: Discussionmentioning
confidence: 99%
“…6 In soft tissue tumors, fluid-fluid levels have been reported in schwannomas, cavernous hemangiomas, and sarcomas (eg, in synovial sarcoma and angiosarcoma, and in malignant fibrous histiocytosis). 5,6 On the basis of viscosity and protein content measurements after hemorrhage or necrosis, fluid-fluid levels are caused by the separation of unclotted blood as opposed to serous (interstitial) fluid.…”
Section: Discussionmentioning
confidence: 99%